Dinâmica da paisagem as áreas protegidas - Ribeiro, Soraya (Universidade do Vale do Rio dos Sinos, 2021)
The loss of biodiversity is common to all ecosystems in the world, in Brazil the situation is no different, where the conversion of natural to agricultural areas is leading to a loss of natural environments in all biomes. One of the alternatives for conserving environments is the creation of protected areas, where a portion of the biome is protected in the midst of a changing environment. Being considered a protected area is not always a guarantee of achieving conservation objectives, as management deficiencies, financial and personnel resources, legal and management aspects do not always manage to make these areas immune from external pressures. This work aims to evaluate two categories of protected areas in Brazil, the Integral Protection Conservation Units and the Ramsar Sites. For this evaluation, a study was carried out using land use as landscape metric, focusing on the interior and buffer zone. This analysis was performed using remote sensing tools using the bases of the Probio (2007), Mapeamento de uso e cobertura vegetal do Rio Grande do Sul: LABGEO-UFRGS (2018) and MapBiomas Collection 3 (2017) projects. The results showed that these protected areas are not immune to external pressures, with many areas presenting anthropic use in their interior incompatible with their category. In the case of Sitios Ramsar, the results showed a good state of conservation and a relationship with the surroundings that served as a shield from anthropic pressures. In the Pampa Biome Conservation Units, the analysis of the integral protection category showed the need to discuss management alternatives for the conservation of natural fields.
Keywords: Ramsar; Unidades de conservação; Pampa; Paisagem; Protected areas; Landscape; ACCNPQ::Ciências Biológicas::Biologia Geral